IMPLEMENTASI KEBIJAKAN PERATURAN PEMERINTAH NOMOR 23 TAHUN 2018 TENTANG PAJAK PENGHASILAN ATAS PENGHASILAN DARI USAHA YANG DITERIMA ATAU DIPEROLEH WAJIB PAJAK YANG MEMILIKI PEREDARAN BRUTO TERTENTU DI KPP PRATAMA KAYU AGUNG - Surya Ibrahim; Octalya Saka; Riky Akbar; Rosita Rosita; Solihin Solihin (MAP Program Pascasarjana Universitas Sjakhyakirti, 2021)
This study analyzes and describes the implementation of Government Regulation Number 23 of 2018 (PP23) concerning Income Tax on Income from Businesses Received or Obtained by Taxpayers Who Have Certain Gross Circulation at the Pratama Kayu Agung Tax Service Office. PP23 is a Government policy that regulates taxpayers' income which is subject to a 0.5% rate with a turnover criterion that does not exceed Rp. 4.8 billion in 1 (one) tax year. The expected results in the implementation of PP23 are the expansion of taxpayer participants, increased compliance, and increased income tax revenues from taxpayers who have a certain gross turnover (MSMEs) so that the opportunity for the welfare of the community increases. The research method used is a qualitative method. The researcher himself is directly involved in the object of this research, namely as participant observation. Data collection techniques are through interviews, observations (observations), and documentation, both on direct (primary) and indirect (secondary) data. Interviews were conducted with the implementors who are employees/officials at KPP Pratama Kayu Agung and to taxpayers as the implementation target group. The results showed that the implementation of PP23 at KPP Pratama Kayu Agung was quite good but not optimal. The communication dimension shows that the transmission of communication in the form of socialization has not been evenly distributed and the resource dimension indicates that it is necessary to add human resources. The number of PP23 tax revenues has grown, but the growth in the number of taxpayers and SPT reporting compliance has decreased. This shows that the implementation of PP23 in KPP Pratama Kayu Agung has produced a fairly good output, but still needs to be improved so that it can produce optimal outcomes.